Pola Komunikasi Interpersonal Mahasiswa Indonesia: (Review of Literature) - Syntia Zhorina Kurniadini; Teguh Dwi Putranto (Jurnal Ilmu Komunikasi, 2025)
The interpersonal communication patterns of Indonesian students play an important role in shaping social interactions, both in academic settings and in everyday life. This study aims to identify and analyze the interpersonal communication patterns that have developed among Indonesian students based on a literature review of various previous studies. The method used in this study is a literature review, analyzing a number of scientific articles in journals. The results of the study show that students’ interpersonal communication patterns are influenced by various factors such as local culture, digital technology development, campus environment, and gender and social background differences. In addition, there has been a shift from face-to-face communication to digital media-based communication, which has an impact on the depth of interpersonal relationships and the quality of interactions